2021
DOI: 10.1002/jum.15714
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Salusin‐α Into Rabbit Carotid Arterial Endothelium Using SonoVue

Abstract: Objectives A new method based on the adhesion of SonoVue to plasmids was assessed to achieve targeted gene delivery into the vascular endothelium. Methods pEGFP‐Salusin‐α and pcDNA3.1‐Salusin‐α plasmids were transfected into the arterial endothelium of different rabbit groups. Western blotting was performed to analyze the expression of EGFP and salusin‐α in the common carotid arteries of rabbits from different groups, and ELISA was performed to detect plasma salusin‐α levels in rabbits from each group; simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Animal experiments have shown that Salusin-α can also inhibit liver steatosis and reduce plasma TG levels in mice ( 16 ). The authors' research group previously established a new method of targeting the delivery of EGFP-Salusin-α plasmid to the arterial endothelia and demonstrated that Salusin-α can reduce atherosclerosis in rabbits ( 17 ), and it was also demonstrated that Salusin-α may inhibit hepatocyte lipid synthesis through the PPARα/ApoA5/sterol regulatory element binding protein-1c (SREBP-1c) pathway ( 18 ). Nevertheless, the exact mechanism by which Salusin-α affects hepatocyte lipid metabolism remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that Salusin-α can also inhibit liver steatosis and reduce plasma TG levels in mice ( 16 ). The authors' research group previously established a new method of targeting the delivery of EGFP-Salusin-α plasmid to the arterial endothelia and demonstrated that Salusin-α can reduce atherosclerosis in rabbits ( 17 ), and it was also demonstrated that Salusin-α may inhibit hepatocyte lipid synthesis through the PPARα/ApoA5/sterol regulatory element binding protein-1c (SREBP-1c) pathway ( 18 ). Nevertheless, the exact mechanism by which Salusin-α affects hepatocyte lipid metabolism remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%